2008
DOI: 10.1074/jbc.m707541200
|View full text |Cite
|
Sign up to set email alerts
|

The KCNQ1 (Kv7.1) COOH Terminus, a Multitiered Scaffold for Subunit Assembly and Protein Interaction

Abstract: The Kv7 subfamily of voltage-dependent potassium channels, distinct from other subfamilies by dint of its large intracellular COOH terminus, acts to regulate excitability in cardiac and neuronal tissues. KCNQ1 (Kv7.1), the founding subfamily member, encodes a channel subunit directly implicated in genetic disorders, such as the long QT syndrome, a cardiac pathology responsible for arrhythmias. We have used a recombinant protein preparation of the COOH terminus to probe the structure and function of this domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
165
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(175 citation statements)
references
References 44 publications
8
165
2
Order By: Relevance
“…Our results from the experiments on C terminus-and N terminus-truncated VSOP suggest that the presence of the cytoplasmic domains is important for the dimerization of VSOP. In fact, the C terminus sequence exhibits a coiled-coil structure that is known to mediate subunit interactions in many examples of ion channel assembly (16)(17)(18). However, because the C terminusand N terminus-truncated VSOP construct still conduct protons, the dimerization does not seem to be necessary for VSOP to function as a proton channel.…”
Section: Discussionmentioning
confidence: 99%
“…Our results from the experiments on C terminus-and N terminus-truncated VSOP suggest that the presence of the cytoplasmic domains is important for the dimerization of VSOP. In fact, the C terminus sequence exhibits a coiled-coil structure that is known to mediate subunit interactions in many examples of ion channel assembly (16)(17)(18). However, because the C terminusand N terminus-truncated VSOP construct still conduct protons, the dimerization does not seem to be necessary for VSOP to function as a proton channel.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be taken into consideration that many tetrameric K ϩ channels are devoid of so called "assembly domain." On the other hand, the isolated C-terminal "assembly domain" of KCNQ forms tetramers spontaneously in vitro (Howard et al, 2007;Wehling et al, 2007;Wiener et al, 2008). It has been suggested that monomers, dimers, and tetramers of AMPAR are in a dynamic equilibrium, and that the pore determines the balance between these intermediates (Greger et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical, spectroscopic, and crystallographic analyses have recently provided the structure model for the C terminus of KCNQ1, which consists of four ␣-helices, helices A, B, C, and D, and an unstructured loop between helices A and B (31). Helices A and B provide binding sites for CaM, and the Cys 445 , the target of S-nitrosylation resides in the midst of the unstructured loop between helix A and B.…”
Section: Discussionmentioning
confidence: 99%